VARK Learning Styles of Bachelor Degree Nursing Students at Boromarajonani College of Nursing, Nakhon Ratchasima Province, Thailand - รูปแบบการเรียนรู้แบบวาร์คของนักศึกษาพยาบาลศาสตรบัณฑิต ในวิทยาลัยพยาบาลบรมราชชนนี นครราชสีมา - ตุ้ยเจริญ, จงกลณี; ทาเสนาะ เอลเทอร์, ปรางทิพย์; หมั่นสระเกษ, รำไพ; สนธิภูมาส, อิสราวรรณ; หมื่นไธสง, ทรงสุดา (Journal of Health Science of Thailand, 2020)
This study aimed to assess the relationship between classes and learning styles of nursing students in a nursing college in Nakhon Ratchasima. Participants were 495 nursing students from the first to the third year of study. Data were collected by using the Learning Style Questionnaire (α=0.82) and analyzed by using descriptive statistics and Chi square test. Research results revealed that the majority of participants were female (94.10%), aged 20.75 years old (SD=1.73). Most of the them preferred multimodal learning styles (89.89%), especially a quadrimodal style (77.37%), which were mostly found among the freshmen (32.73%). The preference on unimodal learning style was observed in 10.10% of the participants who were mainly the third year students (42.0%), and reading or writing (R) was the most preferred (52.0%). There was a significant association between student classes and learning styles (χ2 =1.089, p<0.001). The results could be used as basic information for nursing instructors to design courses congruent with students’ quadrimodal styles. Future research should focus on developing instructional media or pre-training programs for nursing practicum that promote their quadrimodal learning styles.